Clinical Outcome Differences Between Single and Multi-stage Transtibial Amputations. Issue 4 (16th October 2019) - Moon, Daniel; Smith, Kenneth; Shu, Alexander; Challa, Shanthan; Hunt, Kenneth
Category: Diabetes, Trauma, Amputation Introduction/Purpose: Transtibial amputations are often necessary when patients experience irreversible tissue damage in their lower extremities. Current amputation methods incorporate either a single-stage amputation with primary wound closure or a two-stage amputation. A two-stage amputation consists of an initial amputation, typically performed at a more distal site, followed by a second more proximal amputation with stump formalization. The reported advantages of two-staged amputations include decreased muscle retraction and the reduced spread of infection/necrosis. This has been reported to allow for reduced failure rates and lower rates of stump revision. Since two-stage amputations are associated with increased monetary costs, time spent in the hospital, and clinical resources used over single-stage amputations, establishing the differences between the clinical outcomes of both types of amputations can provide benefit-cost insight. Methods: This study was a retrospective study, so we began by pulling a query for all patients that underwent a below-the-knee amputation at our institution from January 1, 2015 through January 1, 2018. We excluded revision amputation patients and patients that suffered a traumatic amputation. We will then perform a chart review while recording demographic data, comorbidities, indication for amputation, labs and culture data if present. We will also record the final outcome of the surgery including any revision surgeries. We will collect data on total length of stay and total cost of care from the date of index surgery to the date of prosthetic fitting. For the cost analysis, a Markov model will be used, which can be incorporated with decision tree modeling to estimate the usage of healthcare resources by determining costs through the different phases of healthcare. Results: Our query returned 152 total patients, of which we estimate approximately 25% to 33% underwent a two staged amputation based on the surgeon's typical amputation preferences. A power analysis was performed which suggested we needed 144 total patients to show a 20% anticipated absolute reduction in complication rates in two-stage amputations compared to single-stage amputations, based on a previous study. We just received the data this week and have not yet performed the full chart review. We hypothesize that two-stage amputations will be considerably more costly than single-stage but that the more involved two-stage strategy may be beneficial in certain subgroups of patients. Conclusion: While we do not yet have the chart review completed for this project, we are excited to elucidate the differences between single-stage and two-stage amputations. We anticipate having all data extracted within the next two months and a complete manuscript by the beginning of the summer. This project has the strong potential to change clinical practice of how trans-tibial amputations are performed depending on the outcome, revision rates, wound complication rates and total healthcare costs.